Recent developments in ultrasound imaging for neuraxial blockade. Issue 5 (October 2018) - Chin, Ki Jinn
Abstract : Purpose of review: Recent research has shed further light on the place of ultrasound imaging in neuraxial blockade in routine clinical practice, its use in thoracic epidurals, and real-time ultrasound-guided techniques. Recent findings: Compared with the conventional technique of surface landmark palpation, preprocedural ultrasound imaging minimizes technical difficulty associated with lumbar neuraxial blockade in patients with poor-quality surface landmarks. Novice practitioners are able to learn to employ the technique effectively. Safety benefits include a reduction in postprocedural back pain associated with fewer needle passes and a lower risk of procedure-associated bleeding. The advantage of ultrasound is minimal however in patients with easily discernible surface landmarks, especially if the practitioner is highly experienced. Recent trials show that preprocedural ultrasound scanning for thoracic epidural insertion reduces needle punctures and increases early analgesic efficacy compared with the palpation technique. Real-time ultrasound-guided techniques, while feasible, remain challenging and may not offer significant benefit over preprocedural imaging in lumbar neuraxial blockade. Their role in thoracic epidural insertion requires further investigation. Summary: Ultrasound imaging of the spine is a valuable technique that, while not indicated for routine use, should be part of the skillset of any practitioner that regularly performs lumbar and thoracic neuraxial blockade.